2016
DOI: 10.1002/bdra.23457
|View full text |Cite
|
Sign up to set email alerts
|

Confined blood chimerism in a monochorionic dizygotic sex discordant twin pregnancy conceived after induced ovulation

Abstract: We report on a case of monochorionic dizygotic twin pregnancy. This observation underlies the need to carefully assess twin pregnancies, especially when obtained after assisted reproductive technology.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
7
0
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 34 publications
0
7
0
1
Order By: Relevance
“…The rare phenomenon of MCDZ twins and blood chimerism has been described both in cattle and humans . Few reports have demonstrated fusion‐susceptibility following artificial reproductive techniques, but spontaneous MCDZ pregnancies like the one seen in this study have also rarely been described. Uncertainties accompany such pregnancies, because placental anastomoses might expose the female fetus to blood products of the male such as anti‐Müllerian hormone and androgens that might masculinize Müllerian derivatives (freemartin effect), such as has been described in cattle.…”
mentioning
confidence: 58%
“…The rare phenomenon of MCDZ twins and blood chimerism has been described both in cattle and humans . Few reports have demonstrated fusion‐susceptibility following artificial reproductive techniques, but spontaneous MCDZ pregnancies like the one seen in this study have also rarely been described. Uncertainties accompany such pregnancies, because placental anastomoses might expose the female fetus to blood products of the male such as anti‐Müllerian hormone and androgens that might masculinize Müllerian derivatives (freemartin effect), such as has been described in cattle.…”
mentioning
confidence: 58%
“…SNP-array analysis of buccal membrane cells revealed a single cell line 46,XX in the twin girl and a single cell line 47,XY,+21 in the twin boy. According to the previous reports [1][2][3], an early fusion of two separately fertilized embryos occurred and the outer masses subsequently formed the placenta. The fusion before implantation lead to a single placenta with vascular anastomosis allowing an intrauterine exchange of cord blood stem cells.…”
Section: Discussionmentioning
confidence: 91%
“…The embryonic lineage remained spatially distinct. This phenomenon exists because of the immaturity of the immunological fetal system [3]. The proportion of chimerism highly depends on the directivity and quantity of vascular anastomosis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Because zygosity diagnosis is not a universal test in twin pregnancy, the knowledge about the prevalence of MCDZ is still limited, and only several case reports have been published in the past . Monochorionic dizygotic twin pregnancies might be closely related to ART . The discussing findings from the publication of Miura and Niikawa suggested that ART techniques could change the cell surface and increase the chance of embryo fusion.…”
Section: Discussionmentioning
confidence: 99%